Coaxial aerogel fiber and preparation method of temperature-adaptive protective aerogel fabric
The coaxial aerogel fiber prepared by coaxial spinning technology uses aramid chopped fibers and nanocellulose fibers combined with phase-change microcapsules to solve the problem of insufficient insulation of traditional fiber fabrics in high temperature environments, and achieves aerogel fiber fabrics with low thermal conductivity and excellent thermal insulation performance, which are suitable for the field of smart wearables.
Patent Information
- Application Number
- CN202411517619.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119615414A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal management aerogel fabrics, and in particular to a method for preparing coaxial aerogel fibers and temperature-adaptive protective aerogel fabrics. Background Art
[0002] With the rapid development of modern science and technology and industry, the public's demand for protection against extreme environmental operations and effective thermal management continues to expand, especially in the fields of aerospace, new energy, electronic equipment, etc., the thermal insulation performance requirements for protective products are becoming increasingly stringent. Although traditional fiber fabrics have certain thermal insulation properties, their thermal insulation efficiency is often difficult to meet the demand in high temperature and high power environments. Therefore, the development of fiber products with ultra-low thermal conductivity and high temperature responsiveness has become one of the current research hotspots.
[0003] Aerogel, as a lightweight material with ultra-high porosity, ultra-low density, ultra-low thermal conductivity and ultra-high specific surface area, is widely used in the field of thermal insulation. Recently, wearable aerogel fiber fabrics used in the field of thermal insulation have made significant progress. The team of Professor Bai Hao and Associate Professor Gao Weiwei of Zhejiang University imitated the core-shell structure of polar bear hair and developed wearable aerogel fiber fabrics with excellent thermal insulation performance. However, the method of manufacturing this artificial fiber is too slow and difficult to mass produce. In addition, patent CN115583829A discloses a low thermal conductivity fiber composite aerogel wet felt and its preparation method, which uses fiber suspension as raw material, uses non-woven molding equipment, and sequentially undergoes deposition, vacuum filtration, spraying sol glue, gel, rolling, supercritical drying and other treatments to obtain a finished fiber composite aerogel wet felt. The obtained wet felt has good compression performance, low density and excellent thermal insulation performance, but the preparation of the wet felt will produce a large amount of wastewater, and the high cost of supercritical drying is not conducive to industrialization. At the same time, due to process limitations, it is not widely used in clothing. In this regard, our research group's patents CN117512809A and CN118480879A use high-performance aramid fibers and renewable, biocompatible cellulose fibers to obtain coaxially structured aramid and cellulose aerogel fibers with good thermal conductivity and good mechanical properties through coaxial spinning needles. The preparation process is simple and can be industrialized on a large scale.
[0004] In recent years, phase change materials have been widely used in fiber fabrics due to their good temperature response performance. Currently, phase change materials can be mixed into fiber fabrics through spinning, but this method has poor adhesion between phase change materials and fibers, and some phase change materials are scattered on the fiber surface, affecting its temperature responsiveness. Summary of the invention
[0005] The present invention provides a method for preparing coaxial aerogel fibers and temperature-adaptive protective aerogel fabrics. The fabrics completely encapsulate phase change microcapsules inside the aerogel fibers. The fabrics have good thermal insulation properties and good mechanical properties. When used in protective products, they have good thermal insulation and warmth-keeping effects. Moreover, the fabrics have excellent low-temperature and high-temperature responsiveness and have good protective effects in extreme environments.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] A coaxial aerogel fiber comprises the following steps:
[0008] S1, weighing aramid short fibers and dissolving them in a polar solvent to obtain a nano-aramid spinning solution;
[0009] S2, weighing nanocellulose powder and dispersing it in deionized water to obtain a nanocellulose dispersion suspension, and then weighing phase change microcapsules and dispersing them in the nanocellulose dispersion suspension to obtain a core layer spinning mixed solution;
[0010] S3, wet spinning the nano-aramid spinning solution and the core layer spinning mixed solution through a coaxial spinning needle, and then fully coagulating in a coagulation bath to obtain a coaxial gel fiber;
[0011] S4, subjecting the coaxial gel fiber prepared above to multiple solvent replacement treatments, washing to neutrality, and finally freeze-drying to obtain the coaxial aerogel fiber.
[0012] Furthermore, the mass fraction of aramid chopped fibers in the nano-aramid spinning solution in S1 is 0.5-5wt%.
[0013] Furthermore, the polar solvent in S1 includes 80-90 wt% of an aprotic solvent and 2-5 wt% of an alkaline substance, wherein the aprotic solvent is one or more of acetonitrile, dimethylformamide, dimethyl sulfoxide, and hexamethylphosphoric triamide, and the alkaline substance is one or more of sodium hydroxide, potassium hydroxide, and potassium tert-butoxide.
[0014] Furthermore, the pretreatment step of the aramid chopped fibers in S1 is: ultrasonically washing the aramid fibers in an ethanol solution, then washing them with deionized water until they are neutral, drying them, and mechanically chopping them into pieces of 1 to 2 cm to obtain aramid chopped fibers.
[0015] Furthermore, the mass fraction of nanocellulose in the nanocellulose dispersion suspension in S2 is 0.1-1 wt %, and the ratio of phase change microcapsules to the nanocellulose dispersion suspension is 1 g: (20-40) mL.
[0016] Furthermore, the needle spinning speed of the nano-aramid spinning stock solution in S3 is 20 to 30 mL / h, and the needle spinning speed of the core layer spinning mixed solution is 30 to 60 mL / h.
[0017] Furthermore, the coagulation bath in S3 is one or more of a weak alkaline solution with a concentration of 15-30wt%, an ethanol solution with a concentration of 15-30wt%, a dimethyl sulfoxide solution with a concentration of 20-30wt%, and an oxalic acid solution with a concentration of 5-10wt%.
[0018] Furthermore, the solidification time in S3 is 10 to 30 minutes.
[0019] Furthermore, the solvent used in the solvent replacement treatment step in S4 is a 25-75 wt % tert-butanol solution, and each replacement time is 6-10 hours.
[0020] The present invention also provides a method for preparing a temperature-adaptive protective aerogel fabric. The temperature-adaptive protective aerogel fabric is obtained by weaving coaxial aerogel fibers.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The coaxial aerogel fiber provided by the present invention has aramid short fibers as the outer layer and nanocellulose fibers and phase change microcapsules as the inner layer to obtain the coaxial aerogel fiber. The phase change microcapsules are coated in the fiber web space of the nanoaramid fibers and the nanocellulose fibers, and the phase change microcapsules form a continuous structure in the fiber web space, which will not affect the thermal conductivity and mechanical properties of the fabric. The thermal conductivity of the fabric prepared by the coaxial aerogel fiber is as low as 0.008 W / m·k, and the fabric has good thermal insulation and mechanical properties. It has good thermal insulation and warmth-keeping effects when used in protective products. In addition, the fabric has excellent low-temperature and high-temperature responsiveness and has good protective effects in extreme environments, thus opening up a new path for the field of smart wearables.
[0022] (2) In the present invention, by adjusting the amount and proportion of phase change microcapsules added to the nanocellulose dispersion suspension, the thermal conductivity, mechanical properties and high and low temperature response performance of the aerogel fiber fabric can be adjusted, so that the prepared fabric has good comprehensive performance; at the same time, in the present invention, by adjusting the needle spinning speed of the nano-aramid spinning stock solution and the core layer spinning mixed solution, it is ensured that the phase change microcapsules are intactly filled in the interior of the aerogel fiber, thereby ensuring the fiber molding and temperature control effects.
[0023] (3) The coaxial aerogel fibers prepared by the present invention are arranged regularly, have a tight structure and are not easy to loosen, and maintain a good shape even at high temperatures, which can meet the needs of practical applications. In addition, the preparation method of the temperature-adaptive protective aerogel fabric is relatively simple to operate, has good repeatability, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the phase change microcapsules purchased from the market in the present invention;
[0025] Figure 2 is a SEM image of the coaxial aerogel fiber prepared in Example 1;
[0026] Figure 3 This is a physical picture of the temperature-adaptive protective aerogel fabric prepared in Example 1;
[0027] Figure 4 The mechanical properties test results of the fabrics prepared in Examples 1-4 and Comparative Examples 1-2;
[0028] Figure 5 This is a photo of the protection of the cotton felt in Comparative Example 1 and the temperature-adaptive protective aerogel fabric prepared in Example 1 under the burning of an alcohol lamp;
[0029] Figure 6 This is a diagram of a thermal insulation test experiment of the temperature-adaptive protective aerogel fabric prepared in Example 1;
[0030] Figure 7 This is a graph showing the low temperature responsiveness test results of the fabrics prepared in Examples 1-4 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0032] Example 1
[0033] This embodiment provides a method for preparing a coaxial aerogel fiber, which specifically includes the following steps:
[0034] S1. Weigh 3g potassium hydroxide, 1.5g laboratory ultrapure water, and 92.5g dimethyl sulfoxide (DMSO) to obtain a polar solvent, weigh 3g aramid short fibers (denier size 2000) to dissolve in the polar solvent, and obtain a nano-aramid spinning solution with a mass fraction of 3wt%; the DMSO used is a Chinese medicine reagent with a purity of 99%;
[0035] Furthermore, the pretreatment steps of the aramid chopped fibers are: ultrasonically washing the aramid fibers in a 75-95wt% ethanol solution for 30-60 minutes, then washing them with deionized water until they are neutral, drying them in an oven, and finally mechanically chopping them into pieces of 1-2 cm to obtain aramid chopped fibers.
[0036] S2. Weigh nanocellulose powder (diameter 40 nm, length 300 μm) and place it in deionized water. After ultrasonic dispersion for 60 min, obtain a nanocellulose dispersion suspension. The mass fraction of nanocellulose in the nanocellulose dispersion suspension is 0.5 wt %. Then weigh 5 g of phase change microcapsules and ultrasonically disperse them in 100 mL of the nanocellulose dispersion suspension to obtain a core layer spinning mixed solution.
[0037] Furthermore, the phase change microcapsules were purchased from the market, and the main component was eicosane, which has a dissolution temperature of about 40 degrees, close to the body temperature of the human body. The electron microscope image is as follows: Figure 1 shown.
[0038] S3, wet spinning the above-mentioned nano-aramid spinning solution at a spinning speed of 25 mL / h and the core layer spinning mixed solution at a spinning speed of 45 mL / h through a coaxial spinning needle, and then coagulating in a coagulation bath for 10 to 30 minutes, and after sufficient coagulation, obtaining a coaxial gel fiber;
[0039] Furthermore, the coagulation bath is one or more of a weak alkaline solution with a concentration of 15 to 30 wt%, an ethanol solution with a concentration of 15 to 30 wt%, a dimethyl sulfoxide solution with a concentration of 20 to 30 wt%, and an oxalic acid solution with a concentration of 5 to 10 wt%; preferably, the weak alkaline solution is one or more of a calcium hydroxide solution, a calcium chloride solution, and a calcium oxide solution.
[0040] S4, the coaxial gel fiber prepared above was placed in a 50wt% tert-butyl alcohol solution for displacement treatment for 8h, the displacement treatment step was repeated 6 times, washed with deionized water until neutral and freeze-dried at -50°C for 2d to obtain a coaxial aerogel fiber, the electron microscope image of which is shown in Figure 2 As shown in the figure, it can be seen that the phase change microcapsules are completely filled in the interior of the aerogel fibers.
[0041] In this embodiment, the coaxial aerogel fibers prepared above are woven using a small prototype loom to obtain a temperature-adaptive protective aerogel fabric, as shown in the figure. Figure 3 shown.
[0042] Embodiments 2 to 4
[0043] The preparation methods of the coaxial aerogel fibers and temperature-adaptive protective aerogel fabrics provided in Examples 2, 3, and 4 are basically the same as those in Example 1, with the only difference being that the ratio of the phase change microcapsules to the nanocellulose dispersion suspension is different. The nanocellulose dispersion suspensions in Examples 1 to 4 are all 100 mL, but the mass of the phase change microcapsules in Example 1 is 5 g, the mass of the phase change microcapsules in Example 2 is 3 g, the mass of the phase change microcapsules in Example 3 is 1 g, and the mass of the phase change microcapsules in Example 4 is 0.5 g.
[0044] Comparative Example 1
[0045] The preparation method of the coaxial aerogel fiber and the temperature-adaptive protective aerogel fabric prepared in Comparative Example 1 is basically the same as that in Example 1, except that phase change microcapsules are not added in Comparative Example 1.
[0046] Comparative Example 2
[0047] The fabric in Comparative Example 2 is a cotton felt having the same thickness as the fabric in Example 1.
[0048] Performance Testing
[0049] 1. The mechanical properties and thermal conductivity of the fabrics in Examples 1 to 4 and Comparative Examples 1 to 2 were tested. The test results are shown in the following table and Figure 4 shown.
[0050]
[0051] It can be seen from Comparative Examples 1 and 2 that the thermal conductivity of the fabric made from the coaxial aerogel fibers prepared from aramid short fibers and nanocellulose is significantly lower than that of the ordinary cotton felt fabric, indicating that the coaxial aerogel fibers prepared from aramid short fibers and nanocellulose have advantages in thermal insulation performance.
[0052] It can be seen from Examples 1 to 4 and Comparative Example 1 that when the amount of phase change microcapsules added is small, the thermal conductivity of the fabric is greater than that when no phase change microcapsules are added, and the thermal insulation performance of the fabric deteriorates. This is because the addition of phase change microcapsules will destroy the complete nanofiber web space structure between the nano-aramid fibers and the nanocellulose fibers, and a small amount of phase change microcapsules do not form a continuous structure, resulting in uneven thermal conductivity of the fabric and poor thermal insulation performance. With the increase in the amount of phase change microcapsules added, the phase change microcapsules form a continuous structure in the nanofiber web space. This continuous structure of phase change microcapsules is filled in the fiber web space, and the temperature can be regulated by absorbing or releasing heat, thereby achieving a good thermal insulation effect. Moreover, after the phase change microcapsules are added, the mechanical properties of the aerogel fibers are not greatly affected.
[0053] 2. Take the cotton felt in comparative example 1 and the temperature-adaptive protective aerogel fabric prepared in example 1 to conduct a high-temperature protection experiment. In the high-temperature protection experiment, the two fabrics have the same thickness at room temperature. The two fabrics are placed on an asbestos net and burned with an alcohol lamp for 30 seconds at high temperature. Figure 5 As shown in the figure, the cotton felt has shrunk, lost its original shape, and no longer has protective ability, while the inner layer structure of the temperature-adaptive protective aerogel fabric prepared in Example 1 remains intact and can still be used at high temperatures, with good high temperature resistance.
[0054] 3. Take the temperature-adaptive protective aerogel fabric prepared in Example 1, place it on a heating plate, increase the temperature of the heating plate, and measure the temperature of the heating plate and the fabric on the heating plate after heating for different times, and conduct a heat insulation test. The heat insulation test data is shown in Figure 6 and the table below.
[0055]
[0056] It can be seen from the above test data that when the heating temperature increases by nearly one-fold, the insulation temperature increases by only one-third, indicating that the temperature-adaptive protective aerogel fabric prepared in Example 1 has excellent thermal insulation performance. The fabric with added phase change microcapsules has a more sensitive temperature effect than the fabric without added phase change microcapsules. As the amount of phase change material added increases, the temperature difference response becomes more obvious.
[0057] 4. The fabrics in Examples 1 to 4 and Comparative Examples 1 to 2 were placed in a low temperature environment and tested for low temperature responsiveness. The test results are as follows: Figure 7 As shown. Figure 7 It can be seen that after adding a small amount of phase change microcapsules, the low-temperature responsiveness of the fabric is worse than that of the aerogel fabric without adding phase change microcapsules, but when the amount of phase change microcapsules reaches 3g, the low-temperature responsiveness of the fabric with phase change microcapsules is better than that of the aerogel fabric without adding phase change microcapsules. This is because in a low-temperature environment, the phase change microcapsules release a certain amount of heat through phase changes, and the phase change microcapsules that form a certain continuous structure in the fiber web release heat more evenly, ensuring the overall low-temperature responsiveness of the fabric.
[0058] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a coaxial aerogel fiber, characterized in that The following steps are involved: S1, weighing aramid short fibers and dissolving them in a polar solvent to obtain a nano-aramid spinning solution; S2, weighing nanocellulose powder and dispersing it in deionized water to obtain a nanocellulose dispersion suspension, and then weighing phase change microcapsules and dispersing them in the nanocellulose dispersion suspension to obtain a core layer spinning mixed solution; S3, wet spinning the nano-aramid spinning solution and the core layer spinning mixed solution through a coaxial spinning needle, and then fully coagulating in a coagulation bath to obtain a coaxial gel fiber; S4, subjecting the coaxial gel fiber prepared above to multiple solvent replacement treatments, washing to neutrality, and finally freeze-drying to obtain the coaxial aerogel fiber.
2. The method for preparing the coaxial aerogel fiber according to claim 1, characterized in that: The mass fraction of aramid chopped fibers in the nano-aramid spinning solution in S1 is 0.5-5wt%.
3. The method for preparing the coaxial aerogel fiber according to claim 1, characterized in that: The polar solvent in S1 includes 80-90wt% of aprotic solvent and 2-5wt% of alkaline substance, wherein the aprotic solvent is one or more of acetonitrile, dimethylformamide, dimethyl sulfoxide, and hexamethylphosphoric triamide, and the alkaline substance is one or more of sodium hydroxide, potassium hydroxide, and potassium tert-butoxide.
4. The method for preparing the coaxial aerogel fiber according to claim 1, characterized in that: The pretreatment steps of the aramid chopped fibers in S1 are: ultrasonically washing the aramid fibers in an ethanol solution, washing them with deionized water until they are neutral, drying them, and mechanically chopping them into pieces of 1 to 2 cm to obtain aramid chopped fibers.
5. The method for preparing the coaxial aerogel fiber according to claim 1, characterized in that: The mass fraction of nanocellulose in the nanocellulose dispersion suspension in S2 is 0.1-1 wt %, and the ratio of phase change microcapsules to the nanocellulose dispersion suspension is 1 g: (20-40) mL.
6. The method for preparing the coaxial aerogel fiber according to claim 1, characterized in that: The needle spinning speed of the nano-aramid spinning stock solution in S3 is 20-30 mL / h, and the needle spinning speed of the core layer spinning mixed solution is 30-60 mL / h.
7. The method for preparing the coaxial aerogel fiber according to claim 1, characterized in that: The coagulation bath in S3 is one or more of a weak alkaline solution with a concentration of 15-30wt%, an ethanol solution with a concentration of 15-30wt%, a dimethyl sulfoxide solution with a concentration of 20-30wt%, and an oxalic acid solution with a concentration of 5-10wt%.
8. The method for preparing the coaxial aerogel fiber according to claim 1, characterized in that: The solidification time in S3 is 10 to 30 minutes.
9. The method for preparing the coaxial aerogel fiber according to claim 1, characterized in that: The solvent used in the solvent replacement treatment step in S4 is a 25-75 wt % tert-butyl alcohol solution, and the replacement time for each time is 6-10 hours.
10. A method for preparing a temperature-adaptive protective aerogel fabric, characterized in that: The temperature-adaptive protective aerogel fabric is obtained by weaving the coaxial aerogel fibers according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-heat-conductivity-coefficient fiber composite aerogel wet felt and preparation method thereof
CN115583829A
Aramid fiber and cellulose aerogel fiber with coaxial structure and preparation method of aramid fiber and cellulose aerogel fiber
CN117512809A
Phase-change temperature-adjusting Lyocell fiber and preparation method thereof
CN117904735A
Radiation refrigeration phase-change thermal insulation material with temperature self-adaptive adjustment capability and preparation method of radiation refrigeration phase-change thermal insulation material
CN118027522A
Nanofiber with aerogel coating layer and preparation method thereof
CN118480879A
Cited By
Aramid fiber aerogel insulation board and preparation method thereof
CN119912726A
High-temperature phase-change heat-insulation ceramic fiber aerogel and preparation method thereof
CN119954517A